Glass polymorphism in glycerol–water mixtures: II. Experimental studies. Issue 16 (5th April 2016) - Bachler, Johannes; Fuentes-Landete, Violeta; Jahn, David A.; Wong, Jessina; Giovambattista, Nicolas; Loerting, Thomas
Abstract : We here study pressure-induced amorphization and polyamorphic transitions in frozen bulk glycerol–water solutions experimentally. Abstract : We report a detailed experimental study of (i) pressure-induced transformations in glycerol–water mixtures at T = 77 K and P = 0–1.8 GPa, and (ii) heating-induced transformations of glycerol–water mixtures recovered at 1 atm and T = 77 K. Our samples are prepared by cooling the solutions at ambient pressure at various cooling rates (100 K s −1 –10 K h −1 ) and for the whole range of glycerol mole fractions, χ g . Depending on concentration and cooling rates, cooling leads to samples containing amorphous ice ( χ g ≥ 0.20), ice ( χ g ≤ 0.32), and/or "distorted ice" (0 < χ g ≤ 0.38). Upon compression, we find that (a) fully vitrified samples at χ g ≥ 0.20 do not show glass polymorphism, in agreement with previous works; (b) samples containing ice show pressure-induced amorphization (PIA) leading to the formation of high-density amorphous ice (HDA). PIA of ice domains within the glycerol–water mixtures is shown to be possible only up to χ g ≈ 0.32 ( T = 77 K). This is rather surprising since it has been known that at χ g < 0.38, cooling leads to phase-separated samples with ice and maximally freeze-concentrated solution of χ g ≈ 0.38. Accordingly, in the range 0.32 < χ g < 0.38, we suggest that the water domains freeze into an interfacial ice, i.e., a highly-distorted form of layered ice, which is unable to transform to HDA upon compression. Upon heating samples recovered at 1 atm, we observe a rich phase behavior. Differential scanning calorimetry indicates that only at χ g ≤ 0.15, the water domains within the sample exhibit polyamorphism, i.e., the HDA-to-LDA (low-density amorphous ice) transformation. At 0.15 < χ g ≤ 0.38, samples contain ice, interfacial ice, and/or HDA domains. All samples ( χ g ≤ 0.38) show: the crystallization of amorphous ice domains, followed by the glass transition of the vitrified glycerol–water domains and, finally, the melting of ice at high temperatures. Our work exemplifies the complex "phase" behavior of glassy binary mixtures due to phase-separation (ice formation) and polyamorphism, and the relevance of sample preparation, concentration as well as cooling rates. The presence of the distorted ice (called "interphase" by us) also explains the debated "drift anomaly" upon melting. These results are compatible with the high-pressure study by Suzuki and Mishima indicating disappearance of polyamorphism at P ≈ 0.03–0.05 GPa at χ g ≈ 0.12–0.15 [ J. Chem. Phys., 2014, 141, 094505].